Chinese tourists’ intention to visit Malaysia in the post-pandemic era: a mixed method approach - Xiaocong, Jiang (2025)
In the post-pandemic era, the global tourism industry faced both challenges and opportunities. This study investigates Chinese tourists’ intentions to visit Malaysia, a country that experienced a significant decline in Chinese arrivals due to COVID-19. Although Malaysia had historically strong tourism ties with China, its recovery has been slower than that of regional competitors. This research explores the key factors influencing Chinese tourists' intention to revisit Malaysia. Using a Mixed Methods Research (MMR) approach, it combines qualitative data from semi-structured interviews and quantitative survey results. Thematic and multivariate regression analyses were conducted within a Concurrent Triangulation Design (CTD). Findings show that Malaysia's tourism image remains positive among Chinese tourists, especially due to cultural affinity and natural attractions. However, concerns regarding health safety and service quality have emerged as new barriers. Quantitative results confirm that the perceived tourism image, destination attractiveness, and competitiveness significantly influenced travel intentions. Cultural attractions, ecotourism, and culinary experiences are major components of Malaysia’s appeal. The study contributes theoretically by extending tourism behavior models to include postpandemic factors such as health safety and service quality. Methodologically, it highlights the effectiveness of mixed methods in capturing complex tourist behaviors. Practically, the research offers recommendations for tourism stakeholders: improving multilingual and cultural training for service staff, addressing regional disparities in infrastructure and promotions, and designing personalized tourism products that meet Chinese tourists’ expectations for culturally rich and safe experiences. It also emphasizes the need for targeted digital marketing through platforms like WeChat, Xiaohongshu (RED), and Douyin (TikTok) to reconnect with Chinese travelers. Future research should broaden the geographical scope to validate findings across different cultural contexts, employ advanced tools such as sentiment analysis and text mining, and update insights regularly to reflect emerging tourism trends, particularly in sustainability and digital innovation.